(untitled) (Comprehensive Journal of Science, 2025)
The emergence of antibiotic-resistant pathogens necessitates exploration of alternative therapeutics. This study evaluated the antibacterial potential of ethanolic extracts from Zingiber officinale (ginger) rhizomes and Syzygium aromaticum (clove) flower buds against clinically isolated Staphylococcus aureus (including MRSA) and Escherichia coli (including ESBL-producing strains) using standardized microbiological assays. Disk diffusion results demonstrated significant antibacterial activity, with clove extract (5% w/v) exhibiting the highest efficacy against S. aureus (21.67±2.89 mm inhibition zone), followed by ginger extract (15.00±4.36 mm at 10% w/v). Against E. coli, clove flowers showed moderate activity (20.00±5.00 mm), while ginger displayed limited effect (3.33±1.53 mm at 10% w/v). Broth microdilution assays revealed MIC values of 25-100 μg/mL and MBC values of 0.15-0.73 μg/mL. Comparative analysis with standard antibiotics (ampicillin, gentamicin, streptomycin) indicated that while streptomycin remained most effective (30.67±2.08 mm), plant extracts demonstrated comparable activity to ampicillin against Gram-positive pathogens. These findings substantiate the potential of ginger and clove extracts as complementary antimicrobial agents, particularly against drug-resistant Gram-positive bacteria, while showing the need for further investigation of their mechanisms and potential synergies with conventional antibiotics.